2022
DOI: 10.1186/s43055-022-00775-3
|View full text |Cite
|
Sign up to set email alerts
|

CMR parameters and CMR-FT in repaired tetralogy of Fallot

Abstract: Background Repaired tetralogy of Fallot patients develops postoperative complications that are in need for follow-up and re-intervention in some circumstances. CMR myocardial feature tracking is a novel method that allows quantification of bi-atrial and bi-ventricular mechanics of deformation. So our aim is to assess the added value of cardiac magnetic resonance imaging and its advanced feature tracking analysis in evaluation of repaired tetralogy of Fallot patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The study of Attalla et al (11) showed less than one-third of patients 16 out of 56 are associated with branch stenosis LPA and/or RPA (representing 28.5% from total patients), in which 12 patients had LPA branch stenosis and 12 had RPA branch stenosis and 8 of them had both branch stenosis. Unlike the present study results that showed more than half of the patients 19 out of 30 are associated with branch pulmonary stenosis (representing 63.3% from total patients) as 9 patients had LPA stenosis (30%), and 10 patients (33.3%) had RPA stenosis.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The study of Attalla et al (11) showed less than one-third of patients 16 out of 56 are associated with branch stenosis LPA and/or RPA (representing 28.5% from total patients), in which 12 patients had LPA branch stenosis and 12 had RPA branch stenosis and 8 of them had both branch stenosis. Unlike the present study results that showed more than half of the patients 19 out of 30 are associated with branch pulmonary stenosis (representing 63.3% from total patients) as 9 patients had LPA stenosis (30%), and 10 patients (33.3%) had RPA stenosis.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding valvular regurgitation, the study of Attalla et al (11) showed the majority of patients 54 out of 56 patients showed pulmonary regurgitation (representing 96.4%). Similar to the present study, where the majority of patients 29 out of 30 (96.6%) had MPA regurgitation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations